Local Treatment of the Primary Tumor for Patients With Metastatic Cancer (PRIME-TX): A Meta-Analysis. - Ryckman, Jeffrey M.; Thomas, Toms V.; Wang, Ming; Wu, Xue; Siva, Shankar; Spratt, Daniel E.; Slotman, Ben; Pal, Sumanta; Chapin, Brian F.; Fitzal, Florian; Soran, Atilla; Bex, Axel; et al. (International Journal of Radiation Oncology, Biology, Physics, 2022)
Purpose: Local treatment of the primary tumor for patients with metastases is controversial, and prospective data across many disease sites have conflicting conclusions regarding benefits.Methods and Materials: A comprehensive search was conducted in PubMed/MEDLINE including randomized controlled trials (RCTs) published in the past 50 years. Inclusion criteria were multi-institutional RCTs of patients with metastatic disease receiving systemic therapy randomized to addition of local treatment to the primary tumor. Two primary outcome measures, overall survival (OS) and progression-free survival (PFS), were quantitatively assessed using random effects, and meta-analyses were conducted using the inverse variance method for pooling. Secondary endpoints were qualitatively assessed and included toxicity and patient-reported quality of life. Exploratory analyses were performed by treatment type and volume of disease.Results: Eleven studies comprising 4952 patients were included (1558 patients received radiation therapy and 913 patients received surgery as primary tumor treatment). OS and PFS were not significantly improved from treatment of the primary (OS: hazard ratio [HR], 0.91; 95% confidence interval [CI], 0.80-1.05; PFS: HR, 0.88; 95% CI, 0.72-1.07). Assessment of primary local treatment modality demonstrated a significant difference in summary effect size on PFS between trials using surgery (HR, 1.15; 95% CI, 0.99-1.33) compared with radiation therapy (HR, 0.73; 95% CI, 0.56-0.96) as the local treatment modality (P = .005). In low metastatic burden patients, radiation therapy was associated with significantly improved OS (HR, 0.67; 95% CI, 0.52-0.85), but surgery was not associated with improved OS compared with no local treatment (HR, 1.12; 95% CI, 0.94-1.34).Conclusions: In RCTs conducted to date enrolling a variety of cancer types with variable metastatic burden, there is no consistent improvement in PFS or OS from the addition of local therapy to the primary tumor in unselected patients with metastatic disease. Carefully selected patients may derive oncologic benefit and should be discussed in tumor boards. Future prospective studies should aim to further optimize patient selection and the optimal systemic and local therapy treatment types.